Sources and consequences of mismatch between leaf disc and whole‐leaf leaf mass per area (LMA) - Maenpuen, Phisamai; Katabuchi, Masatoshi; Onoda, Yusuke; Zhou, Cong; Zhang, Jiao‐Lin; Chen, Ya‐Jun (American journal of botany, 2022)
Premise Leaf mass per area (LMA), which is an important functional trait in leaf economic spectrum and plant growth analysis, is measured from leaf discs or whole leaves. Differences between the measurement methods may lead to large differences in the estimates of LMA values. Methods We examined to what extent estimates of LMA based on whole leaves match those based on discs using 334 woody species from a wide range of biomes (tropics, subtropics, savanna, and temperate), whether the relationship varied by leaf morphology (tissue density, leaf area, leaf thickness), punch size (0.6‐ and 1.0‐cm diameter), and whether the extent of intraspecifc variation for each species matches. Results Disc‐based estimates of species mean LMA matched the whole‐leaf estimates well, and whole‐leaf LMA tended to be 9.69% higher than leaf‐disc LMA. The ratio of whole‐leaf LMA to leaf‐disc LMA was higher for species with higher leaf tissue density and larger leaves, and variance in the ratio was greater for species with lower leaf tissue density and thinner leaves. Estimates based on small leaf discs also inflated the ratio. The extent of the intraspecific variation only weakly matched between whole‐leaf and disc‐based estimates (R2 = 0.08). Conclusions Our results suggest that simple conversion between whole‐leaf and leaf‐disc LMA is difficult for species obtained with a small leaf punch, but it should be possible for species obtained with a large+ leaf punch. Accurately representing leaf traits will likely require careful selection between leaf‐disc and whole‐leaf traits depending on the objectives. Quantifying intraspecific variation using leaf discs should be also considered with caution.